In vivo microvascular and macrovascular endothelial function is not associated with circulating dimethylarginines in patients with rheumatoid arthritis: a prospective analysis of the DRACCO cohort. (18th May 2016) - Dimitroulas, Theodoros; Sandoo, Aamer; Hodson, James; Smith, Jacqueline P.; Kitas, George D.
ABSTRACT: Objectives: To examine associations between asymmetric (ADMA), symmetric dimethylarginine (SDMA) and ADMA:SDMA ratio with assessments of endothelial function and coronary artery perfusion in RA patients. Methods: ADMA and SDMA levels were measured in 197 RA individuals [144 (77.4%) females, median age: 66 years (quartiles: 59–73)]. Patients underwent assessments of microvascular endothelium-dependent and endothelium-independent function, macrovascular endothelium-dependent and endothelium-independent function and vascular morphology (pulse wave analysis, carotid intima-media thickness (cIMT), and carotid plaque). Coronary perfusion was assessed by subendocardial viability ratio (SEVR). Results: SEVR correlated with SDMA ( r  = 0.172, p  = 0.026) and ADMA:SDMA ( r = −0.160, p  = 0.041) in univariable analysis, but not in multivariable analysis accounting for confounding factors. Neither ADMA:SDMA ratio nor SDMA were significantly correlated with microvascular or macrovascular endothelial function, or with arterial stiffness and cIMT. Within subgroup of patients ( n  = 26) with high inflammatory markers, a post-hoc analysis showed that SDMA and the ADMA:SDMA ratio were significantly associated with endothelium-dependent microvascular function in univariable analysis, with Pearson's r correlation coefficients of −0.440 ( p  = 0.031) and 0.511 ( p  = 0.011), respectively. Similar finding were established between ADMA:SDMA ratio and arterial stiffness in univariable analysis, with Pearson's r of 0.493, ( p  = 0.024). Conclusion: Dimethylarginines were not found to be significantly associated with several assessments of vascular function and morphology in patients with RA, however, post-hoc analysis indicates that there may be associations in patients with raised inflammatory markers. Our results suggest that dysregulated NO metabolism may not be the sole mechanism for the development of preclinical atherosclerosis in RA.